Notes on the genus Paraxizicus Gorochov & Kang, 2007 (Orthoptera: Tettigoniidae: Meconematinae) from China - Shi, Fu-Ming; Bian, Xun; Chang, Yan-Lin (Zootaxa, 2011)
The Chinese species of the genus Paraxizicus Gorochov & Kang are reviewed and a key is presented. Two new species are described: Paraxizicus trilobus sp. nov. and Paraxizicus singulus sp. nov.. One known species Xiphidiopsis forcipa Shi & Chen, 2002 is transferred to Paraxizicus. The type specimens are kept in the Museum of Hebei University.